A diagnostic dilemma: enterolith formation secondary to stricture and subsequent bowel obstruction: a case report - Jadhav, Pradnya S.; Hedawoo, Jagadish B.; Changole, Sanjay S.; Soni, Mahesh K.; Lalwani, Adarsh; Kamble, Akhilesh (International Surgery Journal, 2024)
We report a case of a 67 years male patient who presented with complaints of pain in abdomen, loose motions since 3 months and distension of abdomen since 1 day. At the time of admission patient was vitally stable, with no history of vomiting and constipation. Plain x-ray abdomen erects showed evidence of approximately 4-5 radio opaque foreign bodies in the abdomen. Contrast Enhanced computed tomography (CECT) of abdomen revealed multiple ileal strictures with closed loop obstruction with large monoliths. Exploratory laparotomy confirmed 7 ileal strictures each 10 cm apart with proximal dilatation. Resection of ileal stricture was performed and ileoileal anastomosis done. The resected segment contained seven hard, black enteroliths.